INFORMATION SYSTEM SECURITY AUDIT USING ISO/IEC 27002:2013 AT UNIVERSITY OF XXX - Santi, Rusmala; Alfresi, Aminullah Imal; Octariana, Betha (Jurnal Teknik Informatika (Jutif), 2023)
Information system security audit to find out how the current information system security process is implemented, whether it has been implemented in accordance with information security management system standards. The purpose of this study is to examine the suitability of the current information system security process with the ISO/IEC 27002:2013 security standard and to assess the level of capability and maturity of information system security at university of XXX. This audit research resulted in the finding that the information system security process at university of XXX is currently not in accordance with the ISO/IEC 27002:2013 security standard and is at level 2 (managed) with a capability level value of 1,96 and a maturity level of 2,34.